2006
DOI: 10.1158/1055-9965.epi-05-0931
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Atrophic Gastritis in Different Parts of the World

Abstract: Chronic atrophic gastritis (CAG) is a well-established precursor of intestinal gastric cancer, but epidemiologic data about its occurrence are sparse. We provide an overview on studies that examined the prevalence of CAG in different parts of the world. Articles containing data about the prevalence of chronic atrophic gastritis in unselected population samples and published until November 2005 were identified by searching the MEDLINE database. Furthermore, the references in the identified publications were scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
89
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 80 publications
6
89
1
2
Order By: Relevance
“…Taking the short follow-up into account, this finding could partly be due to impaired cobalamin status in atrophic gastritis (58) that often precedes gastric cancer (57). Our data support this hypothesis as the associations between cobalamin and its marker MMA and gastric cancer were confined to the cancer cases with serologic evidence of severe chronic atrophic gastritis.…”
Section: Discussionsupporting
confidence: 65%
“…Taking the short follow-up into account, this finding could partly be due to impaired cobalamin status in atrophic gastritis (58) that often precedes gastric cancer (57). Our data support this hypothesis as the associations between cobalamin and its marker MMA and gastric cancer were confined to the cancer cases with serologic evidence of severe chronic atrophic gastritis.…”
Section: Discussionsupporting
confidence: 65%
“…The highest percentage of cases were diagnosed at advanced stages (stage III and IV) due to non-specific symptoms and an inadequate screening program. Gastric carcinogenesis is a continuous process from non-atrophic gastritis leading to chronic atrophic gastritis (CAG), to intestinal metaplasia (IM) and dysplasia, and finally to intestinal-type gastric adenocarcinoma (2)(3)(4). A prospective 10-year follow-up study in Japan demonstrated that patients with Helicobacter pylori (H. pylori)-induced chronic active gastritis developed atrophic gastritis, which was observed endoscopically and histologically (5).…”
Section: Introductionmentioning
confidence: 99%
“…Serum PG concentrations measured in certain areas of Asia appear to be higher than those in Western countries. For example, the median PGI levels were >90 µg/l in Shandong, China (25), the mean PGI was >100 µg/l in Hunan, China (17) and Yazd, Iran (24), whereas values were usually <70 µg/l in European countries (4,26). However, a Japanese study by Inoue et al (19) involving 200 patients and a Korean study involving 2,558 patients by Lee et al (27) reported a mean serum PGI:I level of <70 µg/l (56.0 and 63.5 µg/l, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of epidemiological studies on CAG and its risk factors have been cross-sectional [4]. Infection with the gastric bacterium Helicobacter pylori was shown to be strongly associated with CAG in a recently published meta-analysis that relied on cross-sectional data [5].…”
Section: Introductionmentioning
confidence: 99%